A 75,000-y-old Scandinavian Arctic cave deposit reveals past faunal diversity and paleoenvironment - Samuel J. Walker; Aurélie Boilard; Mona Henriksen; Edana Lord; Marius Robu; Jan-Pieter Buylaert; Liselotte M. Takken Beijersbergen; Lene Synnøve Halvorsen; Adriana M. Cintrón-Santiago; Emma Katrin Onshuus; Christopher Alan Cockerill; Gabor Ujvari; et al. (Proceedings of the National Academy of Sciences, 2025)
During the last glacial period (~118 to 11.7 ka), the Arctic has been characterized by a major redistribution of flora and fauna as a consequence of extreme climatic fluctuations, with associated glacial advances and retreats, sea-level changes, and shifting sea ice extent. In the high-latitude regions of Northern Europe that are currently subject to rapid climate warming, we lack a comprehensive understanding of faunal biodiversity in the last glacial period due to the extreme rarity of preserved organic remains. Here, we present a stratified sediment deposit with a diverse faunal composition preserved in a bone-bearing layer in Arne Qvamgrotta, part of the Storsteinhola cave system (68.10° N 16.38° E) in Northern Norway. Chronological analyses of sediments and bones including radiocarbon, optically stimulated luminescence, uranium–thorium, and phylogenetic dating place the faunal assemblage in Marine Isotope Stage 5a (MIS 5a, Odderade interstadial, ~85 to 71 ka). Combining comparative osteology and bulk-bone metabarcoding, we identify 46 taxa, including mammals, birds, and fish, with several species not previously found in Fennoscandia. The fauna implies a nonanalogous cold-adapted coastal community, with close proximity to sea ice and nearby freshwater bodies. Mitogenome analyses of a subset of taxa identify extinct lineages which attest to a lack of habitat tracking and the absence of a local refugium during the subsequent fully glaciated periods. This faunal record demonstrates long-term faunal dynamics and coastal environmental conditions during MIS 5a in the European Arctic.